Tailored reinforcement/matrix interface and thermodynamic mechanism during selective laser melting composites. Issue 7 (2nd May 2016) - Dai, D.H.; Gu, D.D.
Abstract : The simulation of thermodynamic behaviours of reinforcing particles and reinforcement/matrix interface during selective laser melting of particle reinforced metal matrix composites was presented. The transition from powder to solid phase, the surface tension and the density change were taken into account. It showed that the operating temperature and the resultant turbulent intensity increased with increasing the applied linear energy density, giving rise to the high instability of the molten pool. The gravity and capillary forces play a crucial role in the rearrangement and the attendant distribution state of the reinforcing particles. The particle morphology and distribution state in the as processed parts were experimentally studied, which were in good agreement with the results predicted by simulation.